Element-sensitive X-ray imaging and computed tomography using energy-selective photodetection - Nüesch, Joachim (My University, 2010)
A new method in X-ray imaging is presented and a proof of concept shown. The proof of concept is done with the simultaneous identification of aluminum, silicon and titanium and the determination of its integrated density. Also some additional measurements are conducted with aqueous solutions. In this case the concentration of sodium chloride and calcium chloride is measured. The method works in transmission and with a spectral analysis of the absorbed photons. The result is an elemental distribution in the path of the X-ray photons. The concept has no strict limit of the number of elements simultaneously detectable. In this work only a single spectrometer is used. The detector can be extended to an array of spectrometers. The method can also be combined with tomography. In this case it is possible to calculate the density of the elements in the voxels of the reconstruction. The method works in photoabsorption and is therefore optimized for thin biological samples. Experiments conducted are in the energy range of 10 – 13 keV using a X-ray source with 15 kVp and with a broad spectrum. The sample can be kept under standard conditions which allows measurements on living tissue. Fine effects on the mass-absorption coefficients are measured in order to identify the elements. Because these fine effects are difficult to detect the stability of the system is important. The elemental distribution information can be used to increase the contrast of some conventional images or to identify tissues, cells, or even molecules. Therefore functional informations could be added to the images. This would be a strong increase in the practical value of X-ray images.
Thèse de doctorat : Université de Neuchâtel, 2010
Keywords: rayon-x; transmission; absorption photoélectrique; détection d'élément; microscope; microCT; X-Ray; transmission; photoabsorption; element detection; microscope; microCT